2021
DOI: 10.1016/j.celrep.2021.108803
|View full text |Cite
|
Sign up to set email alerts
|

Tracing cell-type evolution by cross-species comparison of cell atlases

Abstract: Highlights d Single-cell transcriptional data systematically infers cell-type evolution d A roadmap for the origin and diversity of major cell categories d Muscle cells and neurons are conserved cell types d Conserved transcription factor repertoire specifies major cell categories

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 62 publications
2
55
0
Order By: Relevance
“…Single-cell transcriptomics offers an opportunity for comprehensive cross-species and cross-tissues analysis of cell types. A recent study reported that the cell-type could be proposed as "evolutionary units" in comparative cell biology (Wang et al, 2021). In the current study, we propose that the different epithelial cells in mammal lung may evolve from different organs in zebrafish including swim bladder and gill.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Single-cell transcriptomics offers an opportunity for comprehensive cross-species and cross-tissues analysis of cell types. A recent study reported that the cell-type could be proposed as "evolutionary units" in comparative cell biology (Wang et al, 2021). In the current study, we propose that the different epithelial cells in mammal lung may evolve from different organs in zebrafish including swim bladder and gill.…”
Section: Discussionmentioning
confidence: 62%
“…Whether the lung evolves from the gill or the swim bladder is still a controversy based on morphological evidences (Perry and Sander, 2004;Zheng et al, 2011). A recent study reported that the cell types could be proposed as "evolutionary units" in comparative cell biology (Wang et al, 2021). To infer the evolutionary relationship of respiratory system at the single-cell level, we extracted orthologous genes and performed cross-species clustering analysis of zebrafish gill (Z_G), swim bladder (Z_SB) and mouse adult lung (M_AL), fetal lung (M_FL) (Han et al, 2018) (Figures 3A,B and Supplementary Table 3).…”
Section: Cross-species Analysis Of Cell-type Similaritymentioning
confidence: 99%
“…It not only deepens our knowledge of cells but also provides novel insights into evolutionary and developmental biology [3]. Cross-species integration and comparison of scRNA-seq datasets allow us to explore, at single-cell resolution, the origins of cellular diversity and the evolutionary mechanisms that shape cellular form and function [3-11].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, evolutionary divergences are thought to be caused by transcriptional changes of groups of genes that evolve in a modular fashion and are controlled by transcription factors [21]. Extraction and comparison of gene modules between species will provide deep insights into evolutionary conservation and divergences [11, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell data in evolutionary contexts have generally been applied to distantly related taxa (Tosches et al 2018; Hodge et al 2019; Liang et al 2018), typically focusing on cell type diversity (Sebé-Pedrós et al 2018; La Manno et al 2016; Colquitt et al 2021; Feregrino and Tschopp 2021; J. Wang et al 2021). Evolutionary analysis of different cell types across species, particularly on short time scales, has received less attention (Liang et al 2018).…”
Section: Introductionmentioning
confidence: 99%